REDEFINING INDONESIA’S BLASPHEMY LAW IN THE DIGITAL AGE: A HUMAN RIGHTS PERSPECTIVE - Wardana, Khansadhia Afifah; Rahayu, Rahayu; Sukirno, Sukirno (Fakultas Hukum, Universitas Diponegoro, 2024)
This paper aims to examine the cascading impact of current conditions on the freedoms of expression and religious belief within Indonesia's online sphere, particularly amidst a rising trend of religious blasphemy cases. The dynamic nature of social interactions and discussions in cyberspace has fostered diverse interpretations influenced by subjective understandings of religion, often resulting in disputes of religious blasphemy. Employing a qualitative research method, the study analyses pertinent literary sources to provide insights into the practice of blasphemy laws and their detrimental effects on the freedoms of religion and expression. Indonesia, as a signatory of ICCPR and the Rabat Plan of Action, upholds constitutional guarantees of these freedoms. However, the current application of blasphemy regulations needs reform to better safeguard the rights of its citizens. By targeting laws that prohibit incitement to religious hatred, the legal framework can more effectively fulfill its primary objective of protecting people from discrimination and ensuring their dignity. This research underscores the urgency for Indonesia to recalibrate its approach to blasphemy laws, aligning them with international human rights standards. So that Indonesia can enhance its commitment to protecting freedom of expression and religious belief, fostering a more inclusive and rights-respecting environment for its diverse population.